Hemoglobinuria producida por una fístula en la sutura perivalvular post reemplazo con prótesis valvular mitral - Agusti, Régulo (2001)
This is a case of 65 year old male with past medical history significant for coronary artery disease and severe mitral valve prolapse for which he underwent simultaneous coronary artery bypass graft using the saphenous vein, mitral valve replacement with warfarin the patient wa discharged home. Three months postoperatively the patient developed apparent “hematuria”. Physical examination and extensive laboratory analysis were unremarkable in determinig an etiology. After referred, further studies ilustrared a diagnosis of hemoglobinuria. Transthoracic echocardiogram revealed a perivalvular leakage with a normally functioning St. Jude mitral valve replacement. Clinical course was uneventful and the hemoglobinuria resolved spontaneously. This case illustrates the importances in determinig the etiology and pathophysiology of hemoglobinuria with transthoracic and thansesophageal echocardiography.